Analysis of the Performance of Employees at the Environmental and Sanitation Agency of Badung Regency - Komang Ardiana; Ida Ayu Putu Sri Widnyani; I wayan Astawa (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The performance of government agency employees serves as the foundational base that must be established, maintained, and developed within government institutions to ensure a positive impact on both the quality and quantity of government operations. Challenges such as the limited availability of competent human resources, the misalignment between employee placements and their competencies, and a lack of employee discipline have been identified. The purpose of this research is to understand the current performance, the obstacles encountered, and the strategies employed to enhance employee performance. This study utilizes a qualitative descriptive approach. The results indicate that the performance of employees at the Environmental and Sanitation Department of Badung Regency is good in terms of responsiveness and responsibility indicators, but it is not yet fully optimal in terms of productivity and service quality indicators. The obstacles faced in improving employee performance include a lack of employee interest and opportunities to attend technical training aligned with their competencies, limited rotation across departments, minimal communication between leadership and staff, insufficient competent human resources, and inadequate facilities and infrastructure. The strategies for improving employee performance include supporting the implementation of activities as planned, facilitating employee competency development, fostering better communication, allocating budgets for the fulfillment of inadequate facilities and infrastructure, and proposing the recruitment of employees with specialized expertise in waste management.